PENGEMBANGAN BAHAN AJAR BERBASIS ANDROID PADA MATERI TEMUAN KAPAL TENGGELAM DI PERAIRAN INDONESIA UNTUK MENINGKATKAN KEMAMPUAN LITERASI MARITIM SISWA SMAN1 CILEUNGSI - Ismi Novianti; Yuni Maryuni; Tubagus Umar Syarif Hadi Wibowo (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
This research aims to: (1) analyze the need for developing of android-based teaching materials from submerged in Indonesian sea to increase capability maritime literacy of SMA Negeri 1 Cileungsi students; (2) explain the steps for developing android-based teaching materials from submerged in Indonesian sea to increase capability maritime literacy of SMA Negeri 1 Cileungsi students; and (3) determine the effectiveness of the application of android-based teaching materials from submerged in Indonesian sea to increase capability maritime literacy SMA Negeri 1 Cileungsi students. The method used in this research is the development method (R&D) with the ADDIE development model. Sampling was carried out using Purposive Sampling technique. The sample in this study consisted of an experimental class of 35 students and a control class of 35 students. The maritime literacy condition of SMA Negeri 1 Cileungsi students is in the low category, this can be seen from three aspects, namely knowledge, attitudes, and behavior. Then given treatment in the experimental class and control class. Based on the results of data analysis, it shows that there are differences in increase capability maritime literacy of students who use android-based teaching materials from submerged ships findings in Indonesian sea with journal learning resources. The N-gain test results showed the average value of the maritime literacy knowledge test in the experimental class was 0.30 and in the control class was 0.29. The average value of the marine environmental care attitude test in the experimental class was 0.45 and in the control class was 0.35 and the average value of the marine environmental care behavior test in the experimental class was 0.23 and in the control class was 0.16. Thus it can be concluded that the development of android-based teaching materials from submerged ships findings in Indonesian sea can increase capability maritime literacy of SMA Negeri 1 Cileungsi students.